2019
DOI: 10.1108/ec-06-2019-0287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of groove shape on the hydrodynamic lubrication of journal bearing considering cavitation

Abstract: Purpose The purpose of this study is to investigate the influence of groove shape on the hydrodynamic characteristics of a journal bearing. Design/methodology/approach The computational fluid dynamics model also takes into account the cavitation phenomena and thermal effect, which can illustrate the lubrication performance of a journal bearing. Findings The hydrodynamic simulations of the journal bearing with the different groove shapes are conducted under different operation conditions. Originality/valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Yu et al [4] pointed that the cavitation area reduced but the dynamic pressure area enlarged with the decrease of cavitation pressure. Considering the cavitation phenomena and thermal effect, Chen et al [5] gained the hydrodynamic simulations of journal bearing for different groove shapes under different operation conditions. Dhande et al [6] used mixture model to study cavitation and observed that maximum pressure of journal bearing drop when cavitation is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [4] pointed that the cavitation area reduced but the dynamic pressure area enlarged with the decrease of cavitation pressure. Considering the cavitation phenomena and thermal effect, Chen et al [5] gained the hydrodynamic simulations of journal bearing for different groove shapes under different operation conditions. Dhande et al [6] used mixture model to study cavitation and observed that maximum pressure of journal bearing drop when cavitation is considered.…”
Section: Introductionmentioning
confidence: 99%
“…In the research conducted by Li for obtaining accurate result (Li et al, 2020), the CFD method combined with simplified engineering algorithms was used to predict the performance of aerostatic bearings. Considering cavitation, Yu et al (2019) used CFD to study the performance of hydrostatic bearings under different groove shapes. Using FLUENT to simulate the characteristics of the support bearing on the energy recovery device, Xu et al (2016) found that the support force varied linearly with the supply pressure and film thickness and obtained the optimal film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mo et al [ 10 ] also adopted the THD method based on dynamic mesh technology, and urged that it can be applied to simulate the variation of inner temperature HJB, whereas, they also mentioned further experimental verification is still of necessity. For the methods of considering cavitation function, Chen et al [ 11 , 12 ] presented the influence of shape of groove on the lubrication with the cavitation and thermal effect taken into consideration, and provided suggestions for groove shape selection under extreme operation condition, whereas, the viscosity dissipation function was not taken into consideration. Song et al [ 13 ] and Xiang et al [ 14 ] introduced the three-dimensional (3D) models with considering conjugate heat transfer and transient interactions for HJB, separately.…”
Section: Introductionmentioning
confidence: 99%